Variations and Asymmetry in Sacral Ventral Rami Contributions to the Bladder - Rebeccah R. Overton; Istvan P. Tamas; Emily P. Day; Nagat Frara; Michel A. Pontari; Susan B. Fecho; Steven N. Popoff; Mary F. Barbe (Diagnostics)
Background/Objectives: We have demonstrated in human cadavers and canines that nerve transfer to bladder vesical nerve branches is technically feasible for bladder reinnervation after nerve injury. We further clarify here that sacral (S) ventral rami contribute to these vesical branches in 36 pelvic sides (in 22 human cadavers). Methods: Gross post-mortem visualization and open anterior abdominal approaches were used, as was micro-CT of sacral nerve bundles, for further confirmation when needed. Results: Considerable between and within-subject variation was observed. Sacral (S) ventral rami contributions to vesical nerves were observed as shared contributions from several rami or, in a few cases, from single rami: S2 alone (6%), S3 alone (6%), S2 and S3 (28%), S3 and S4 (28%), S2–S4, 14%, L5 in combination with S1–S4 (6%), S1 and S2 (6%), and S3–S5 (3%). The most common contributor to these shared or single rami contributions was from the S3 ventral ramus, which contributed 100% of the time on the left side and 79% on the right side. Side-to-side asymmetry was observed in 10 of 14 cadavers examined bilaterally (71%). Conclusions: This characterization of the anatomical variation in sacral ventral rami contributions to the bladder will ultimately aid in developing therapeutics for patients with bladder dysfunction.